Is simultaneous resection of Meckel's diverticulum beneficial or harmful in bariatric and metabolic surgery? (Annals of Medical Research, 2022)
Aim: To investigate whether complications are different with respect to resection or non-resection of Meckel's diverticulum (MD) detected incidentally during two bariatric and metabolic surgery (BMS) procedures, open sleeve gastrectomy with transit bipartition (SG-TB) with resection of MD (MDR) and open one-anastomosis gastric bypass (OAGB) without MDR.Materials and Methods: This case-control study included patients who received treatment between December 2015 and January 2022. A total of 24 obese patients with type 2 diabetes mellitus diagnosed with MD during open SG-TB surgery (and underwent concurrent MDR) were defined as the MDR positive (MDR-P) group. Ten obese patients without type 2 diabetes mellitus who were found to have MD during open OAGB surgery but did not undergo MDR were defined as the MDR negative (MDR-N) group.Results: The mean age of the MDR-P group was 54.42 ± 10.83, while the MDR-N group had a mean age of 39.50 ± 9.77 years (p = 0.001). 66.7% of the MDR-P group was male, 100.0% of the MDR-N group was female (p < 0.001). Median follow-up time was 24 (IQR = 24 - 36) months for both groups. None of the patients developed intraoperative or postoperative complications related to diverticulectomy (for the MDR-P group) or related to MD (for the MDR-N group).Conclusion: Resection of incidental MD during SG-TB and non-intervention in OAGB did not cause any complications in short and mid-term follow-up. We still think that patients should be informed about the risks of all possibilities and the intervention for MD should be determined according to the patient's decision.
Keywords: Bariatric and metabolic surgery; Meckel's diverticulum; Sleeve gastrectomy with transit bipartition; One anastomosis gastric bypass; Resection